Pemaknaan Kewenangan Mengadili dalam Praktik Peradilan Perdata tentang Permohonan Penetapan Orang Hilang Perspektif Hukum Positif dan Hukum Keluarga Islam - Moch. Choirul Rizal (Institut Agama Islam Negeri (IAIN) Kediri, 2020)
Article 44, paragraph (4) of Law No. 24 of 2013 it is not clear which judicial body has the authority to determine the unclear whereabouts of a person because of missing or dead but his body was not found. For this reason, this research focuses on 2 (two) problems. First, the practice of civil justice regarding applications for the determination of missing persons. Second, the meaning of the authority to adjudicate in the practice of civil justice regarding applications for the determination of missing persons. This research is included in the theoretical research using a statute approach, case approach, and conceptual approach. The results of this study answer 2 (two) problems. First, in examining and adjudicating cases of petition for the determination of missing persons, the general court uses rules regarding the state of absence (afwezig) according to Article 467 and Article 468 of the Civil Code, while religious courts use a legal basis relating to inheritance law. Second, to examine and adjudicate cases for the application of missing persons, the authority of the general court is based on Article 467 and Article 468 of the Civil Code, while the authority of the religious court body still requires interpretation of the judge’s law on the subject matter, namely whether it has a connection with inheritance law or not. The case for appealing the missing person, as long as it is related to inheritance law, can reopen the option for Muslims to choose which judicial body to obtain legal certainty regarding the person’s absence.